2020
DOI: 10.1080/21691401.2019.1709856
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Clostridium difficile toxin B induces colonic inflammation through the TRIM46/DUSP1/MAPKs and NF-κB signalling pathway

Abstract: Clostridium difficile (C. difficile) infection results in toxin-induced epithelial injury and marked colonic inflammation. Mitogen-activated protein kinase (MAPK) and NF-jB which regulated by MAP kinase phosphatase (MKP, also known as dual specificity phosphatases, DUSP) are fundamental signalling pathways that mediate multiple cellular processes. However, the regulation of DUSP/MAPKs and NF-jB pathway in C. difficile-induced colonic inflammation remains unclear. Here, we report that TcdB significantly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Li et al . 77 also showed that these effects were mediated by binding of the TRIM46 to the promoter region of the NF-κBp65 subunit. In addition to pro-inflammatory mediators in acute colitis of CDI, inflammation was further accompanied by infiltration of immune cells.…”
Section: Induction Of Inflammation In the Hostmentioning
confidence: 93%
See 2 more Smart Citations
“…Li et al . 77 also showed that these effects were mediated by binding of the TRIM46 to the promoter region of the NF-κBp65 subunit. In addition to pro-inflammatory mediators in acute colitis of CDI, inflammation was further accompanied by infiltration of immune cells.…”
Section: Induction Of Inflammation In the Hostmentioning
confidence: 93%
“…Li et al . 77 reported the role of a MAP kinase phosphatase DUSP1 on inhibition of the MAPK activity. A knockout mutant of TRIM46, which ubiquitinates DUSP1, could inhibit TcdB-induced MAPK and NF-κB signaling, leading to the repression of TNF-α and IL-1β.…”
Section: Induction Of Inflammation In the Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) The production of high levels of proinflammatory cytokines is necessary. [17][18][19][20][21][44][45][46][47][48] In patients with severe CDI, the systemic inflammatory response (as documented in both patients and experimental animal models) 6,10-13,48,51 is due to not only local tissue damage but also the inflammatory action of the Tcds, [17][18][19][20][21][44][45][46][47][48]52 the structural and metabolic components released by C. difficile itself, and the modification of the intestinal microbial flora following C. difficile-specific therapy; 5,23-26,53-56 (b) Tcds have to reach the systemic circulation (a characteristic limited to only some patients with CDI). [6][7][8][9][10][11][12][13] In these conditions, the interaction between TcdB, TNF-α and IFN-γ can trigger an increase in the toxicity of TcdB and its systemic pathological effects (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…TRIM46 has been known to be involved in inflammatory response through ubiquitination. It ubiquitinates DUSP1 (Dual-specificity phosphatase 1), which in turn induces activation of NF-κB and MAPK (Mitogen-activated protein kinases) in colonic inflammation (Li et al 2020). On the other hand, TRIM46 acts as an oncogene in osteosarcoma by interacting with and ubiquitinating peroxisome proliferator-activated receptor alpha (PPARα), resulting in the activation of the NF-κB signaling pathway (Jiang et al 2020).…”
Section: Introductionmentioning
confidence: 99%